THE IMPACT OF THE DIGITAL ERA ON THE IMPLEMENTATION OF THE TRADITIONAL SIX-SIGMA DMAIC- A NEW DMAISE CYCLE DEVELOPMENT - Saad, Sameh; Bahadori, Ramin; Khamkham, Mohamed; Adi, Karrim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
There is a clearly identified need for adjusting the current implemented standards and methods in the area of process improvement, like Six Sigma, to be aligned with technology advances in the context of Industry 4.0. Thus, this research aims to focus on the Six Sigma DMAIC methodology and introduce a new quality improvement cycle toward Industry 4.0. The proposed new Six Sigma implementation procedure is called the DMAISE (Pronunciation: də-mɛ́jz/də-mayz) improvement cycle, which consists of five main phases: Data Measurement, Analysis, Interpretation, Simulation and Enhancement. DMAISE cycle is introduced to obtain all benefits from the DMAIC while not being affected by its limitations that result from the lack of proper integration of technologies available through the advancements inspired by Industry 4.0. A questionnaire survey is developed to collect data from practitioners, experienced employees, and academics in the available organisations to evaluate and validate the proposed new cycle. The results demonstrated that the proposed cycle is considered a viable quality improvement cycle for the new challenges that arise with the Industry 4.0/digital era and the smart technologies being developed for manufacturing environments.